Use and application of herbal preparations against pebrin disease in Bombyx mori L. populations - Musayeva Maryam Rza,; Verdiyeva Leyla Elman,; Hasanova Lala Akif,; Mammadzade Tural Mehdi,; Mammadova Elmira Musallim,; Babayeva Turkan Mirsakhavat, (The Bioscan, 2025)
The serious threat posed by pebrin disease of mulberry silkworm to sericulture, the limitations of existing control methods, and the relevance of searching for herbal alternatives are substantiated. The aim of the study is to study in the condition in vitro and in vivo effects of selected plant extracts from the rich vegetation of Azerbaijan against pebrin spores and to develop safe and effective herbal preparations for use in sericulture farms. The aim of this study was to evaluate the prevention and treatment of pebrin disease by a number of plant extracts used in traditional medicine (on worms emerging from naturally diseased grenae of the Namazli-2 genus). The diseased grenae had been divided into 3 parts. The first part - worms that were treated with grenae based on the existing methodology and emerged from the affected grenae were given feed soaked in plain water twice a day until the end of feeding. The second part - worms that emerged from the affected grenae were given feed soaked with herbal preparations (wormwood, mint, garlic extract, citric acid) twice a day starting from the first feeding. The third part - worms that emerged from the diseased grenae that were not affected by the preparations were given feed soaked with the above herbal preparations twice a day starting from the first feeding. As a control for the experiment, in 3 repetitions, 150 worms in each repetition, worms that emerged from naturally diseased grenae and also from healthy grenae were fed with leaves soaked in plain water twice a day. While the total mortality from Pebrin disease was 14.23% in the control, this indicator was 4.00-7.00% in the experimental variants. The survival rate of worms was also higher in the experimental variants (94.00-96.00%) compared to the control (85.78). If the cocoon yield from one box was 72.0 kg in the diseased control variant, the cocoon yield increased to 80-85 kg in the trial of herbal preparations.